2015
DOI: 10.1016/j.pnpbp.2015.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Associations between DNA methylation and schizophrenia-related intermediate phenotypes — A gene set enrichment analysis

Abstract: Multiple genetic approaches have identified microRNAs as key effectors in psychiatric disorders as they post-transcriptionally regulate expression of thousands of target genes. However, their role in specific psychiatric diseases remains poorly understood. In addition, epigenetic mechanisms such as DNA methylation, which affect the expression of both microRNAs and coding genes, are critical for our understanding of molecular mechanisms in schizophrenia. Using clinical, imaging, genetic, and epigenetic data of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 122 publications
(113 reference statements)
1
15
0
Order By: Relevance
“…For example, PBX/Knotted 1 Homeobox 1 ( Pknox1 ) has been associated with schizophrenia-related intermediate phenotypes and hippocampal volume (Hass et al, 2015). In addition, genetic mutations in the early growth response 2 ( EGR2 ) transcription factor are linked to schizophrenia and bipolar disorder (Hu et al, 2015; Kim et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, PBX/Knotted 1 Homeobox 1 ( Pknox1 ) has been associated with schizophrenia-related intermediate phenotypes and hippocampal volume (Hass et al, 2015). In addition, genetic mutations in the early growth response 2 ( EGR2 ) transcription factor are linked to schizophrenia and bipolar disorder (Hu et al, 2015; Kim et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies suggest a role for epigenetic mechanisms in the development of psychiatric disorders as well as multiple sclerosis (140,141). Altered methylation pattern of potential risk genes have been associated with both MS (142) and schizophrenia (117,143). As noted above, hypomethylation correlates to reactivation of a range of HERV members in a range of cancers.…”
Section: Dna Methylation and Chromatin Modificationmentioning
confidence: 99%
“…Epigenetic profiles of the hippocampus and the amygdala have been examined in healthy controls and in relation to a range of psychiatric disorders such as schizophrenia and depression. Taking a gene set enrichment approach using methylome-wide data, Hass et al (2015) found altered epigenetic patterns in the hsa-miR-219a-5p microRNA target gene set to correlate with hippocampal volume in a schizophrenia sample. Methylation in the serotonin transporter gene SLC6A4, a risk locus for depression, has been found to associate with hippocampal grey matter volume and parts of the amygdala in healthy controls (Dannlowski et al, 2014).…”
Section: Introductionmentioning
confidence: 99%